Mental health and ART adherence among adolescents living with HIV in Mozambique. Issue 2 (1st February 2023) - Nguyen, Nadia; Lovero, Kathryn L.; Falcao, Joana; Brittain, Kirsty; Zerbe, Allison; Wilson, Ira B.; Kapogiannis, Bill; Pimentel De Gusmao, Eduarda; Vitale, Mirriah; Couto, Aleny; Simione, Teresa Beatriz; Abrams, Elaine J.; et al.
ABSTRACT: Little is known about the mental health needs of adolescents living with HIV (ALWH) in Mozambique, including the potential relationship between mental health challenges and poor antiretroviral treatment (ART) adherence. We examined mental health problems (anxiety, depression, post-traumatic stress disorder [PTSD] symptoms and impairment) and their association with self-reported ART adherence among ALWH ages 15–19 in Nampula, Mozambique. The associations between each mental health problem area and sub-optimal adherence were estimated using logistic regression, controlling for age, education, and social support, with interaction by gender. Males had significantly higher anxiety (5.6 vs 4.3, p  = 0.01), depression (5.8 vs 4.1, p  = 0.005), and PTSD (13.3 vs 9.8, p  = 0.02) symptoms and impairment (1.8 vs 0.56, p <0.0001) scores than females. Proportion reporting sub-optimal adherence (65%) did not differ by gender. Higher anxiety, depression, and PTSD symptom and impairment scores were significantly associated with higher odds of sub-optimal ART adherence in males but not females. Among Mozambican ALWH, mental health problems were prevalent and two-thirds had ART adherence less than 90%. Worse mental health was associated with increased odds of sub-optimal ART adherence in males but not females. Interventions are needed to address mental health problems and improve ART adherence in Mozambican ALWH, particularly among males.